Interfacial Li-Ion Storage between Graphene Layers. (7th July 2017) - Park, Jinho; Perini, Christopher; Liu, Tianyuan; Hankinson, John; Vogel, Eric M; Navaei, Milad; Lee, Seung Woo; Stern, Ilan
Abstract : Here we studied the charge storage mechanism of single and few layer graphene as anodes for lithium-ion batteries. The graphene was synthesized through a chemical vapor deposition process. Through X-ray photoelectron spectroscopy and Raman, the as-synthesized graphene was found not to be oxidized nor to contain defects. To obtain electrodes, the graphene was transferred layer by layer onto a copper substrate. In the electrochemical measurements, the single layer graphene exhibited almost identical cyclic voltammogram and capacity to the bare copper substrate, indicative of incapability for charge storage. However, the charge capacity and capacitance gradually increased with the number of graphene layers when additional graphene sheets were transferred onto the single layer graphene. We also demonstrated that defects introduced through ozone treatment decreased the charge storage performance in terms of coulombic efficiency and stability